Should cartel sanctions be reduced in case the offender runs a corporate compliance program? - Alexander Morell (Leibniz Institute for Financial Research SAFE, 2024)
A bonus on the fine in response to the defendant running a corporate compliance program is superfluous because working leniency programs provide all the incentives necessary to implement efficient compliance. Others opposed to such a bonus argue that unreduced fines are sufficient to incentivize the adoption of effective corporate compliance programs. Proponents, on the other hand, argue that a reduction in fines conditional on running a corporate compliance program incentivizes more investments in compliance. Both arguments are incomplete. It is true that, generally, sanctions alone provide only suboptimal incentives to invest in compliance because some compliance investments (those in detecting infringements, i.e., "policing") can increase the detection probability for cartels that remain. However, leniency programs provide an additional incentive to invest in compliance to find cartels in-house as all cartelists strive for being the first to report. Comparing the two effects shows that under plausible assumptions the latter dominates, rendering a bonus on the fine superfluous.
Keywords: G34; L22; L41; 330; Corporate compliance programs; leniency programs; antitrust sanctioning; corporate governance